Android Implementation of Traditional Indonesia Fashion Application - Tukiyo, Tukiyo; Arifin, Ardian; Dewantara , Rizki; Ratnadewi, Ratnadewi; Anggraini, Julaiha Probo (Politeknik Ganesha Medan, 2023)
Indonesia has been gifted with a wide range of diverse cultures from Sabang to Merauke, making Indonesia one of the biggest country with multi ethnic groups, races and cultures. Meanwhile, a lack of information that can be accessed by the students causing a big issue that needs to be addressed. The information of Indonesian traditional clothing is very limited, which has been represented as a characteristic of tribe and culture in each region and also used in the traditional ceremony. Therefore, this study aims to develop an Android-based educational game of traditional Indonesian clothing. The method used in this study was Research and Development approach. The results of this study showed that developing an educational game